ali48
ali48
16-07-2017
Mathematics
contestada
F(x) =x^2+6x and g(x)=7-x find (f-g)(x) and (f-g)(9)
Respuesta :
Nick911
Nick911
16-07-2017
f(x)=x²+6x
g(x)=7-x
(f-g)(x) means that f(x)-g(x), so
f(x)-g(x)
=x²+6x-7+x
Combining like terms
x²+6x+x-7
=x²+7x-7, so (f-g)(x)=x²+7x-7
Next,
(f-g)(x)
=x²+7x-7
(f-g)(9)
=(9)²+7(9)-7
=81+63-7
=144-7
=137, so (f-g)(9)=137. Hope it help!
Answer Link
VER TODAS LAS RESPUESTAS ( 12+ )
ACCESS MORE
Otras preguntas
A government bond with a coupon rate of 7% makes semiannual coupon payments on January 15 and July 15 of each year. The Wall Street Journal reports the asked pr
express 0.0706 to standard form
It shivered the window, pane and sash; It rent the banner with seam and gash. What are TWO words the author could use to replace the term rent without changing
Help me please thank you
1 lb = 16 oz. How many lbs (pounds) are in 14 oz (ounces)?
5) What is the empirical formula of a compound containing 47.37% carbon, 10.59% hydrogen, and 42.04% oxygen?
Can you come up with a mathematical relationship, based on your data that shows the relationship between distance from the charges and electric field strength?
You are fortunate to receive multiple job offers after graduating from college. You find the decision-making very difficult, but once you decide on an offer to
You have just replaced the ink cartridge in an inkjet printer. What should you do immediately after this?
number added to the difference between triple the number and thirteen Translate into a variable expression. (Use x for your variable. Do not simplify.)